2019
DOI: 10.1002/etc.4419
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of a Large and Representative Sample of Antarctic Marine Invertebrates to Metals

Abstract: There are limited data on the sensitivity to contaminants of marine organisms in polar regions. Consequently, assessments of the risk of contaminants to marine biota in polar environments typically include extrapolations from temperate and/or tropical species. This is problematic because the taxonomic composition of organisms differs between polar and temperate/tropical waters, and both the toxicity of chemicals and the physiology of organisms are very different at the stable low temperatures experienced in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Toxicity data are commonly obtained from laboratory toxicity tests used to estimate median lethal concentrations (e.g., LC 50 ) of a test population, which are often used in ecological risk assessments . Previous studies have shown that the sensitivity of different species exposed to the same metal varies greatly and has been correlated to body size, evolutionary patterns, and physicochemical and physiological characteristics. Similarly, the variation in toxicity of a single species when exposed to different metals can be orders of magnitude greater. For example, the 96-h-LC 50 values for Cu, Cd, Zn, and Pb were 0.006, 0.10, 0.46, and 0.63 mg/L for cyprinidae (Rasbora sumatrana) and 0.038, 0.17, 1.06, and 1.99 mg/L for guppy (Poecilia reticulata), respectively . In addition, evidence suggests that of the four metals, Cu is the most toxic to zebrafish, freshwater mussels, and invertebrates (e.g., Daphnia magna). , The ability of metal to compete with biological binding targets and metal speciation in the exposure medium play an important role in metal toxicity. , The affinity of different metals to biotic ligands correlates to their toxicity to aquatic organisms .…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity data are commonly obtained from laboratory toxicity tests used to estimate median lethal concentrations (e.g., LC 50 ) of a test population, which are often used in ecological risk assessments . Previous studies have shown that the sensitivity of different species exposed to the same metal varies greatly and has been correlated to body size, evolutionary patterns, and physicochemical and physiological characteristics. Similarly, the variation in toxicity of a single species when exposed to different metals can be orders of magnitude greater. For example, the 96-h-LC 50 values for Cu, Cd, Zn, and Pb were 0.006, 0.10, 0.46, and 0.63 mg/L for cyprinidae (Rasbora sumatrana) and 0.038, 0.17, 1.06, and 1.99 mg/L for guppy (Poecilia reticulata), respectively . In addition, evidence suggests that of the four metals, Cu is the most toxic to zebrafish, freshwater mussels, and invertebrates (e.g., Daphnia magna). , The ability of metal to compete with biological binding targets and metal speciation in the exposure medium play an important role in metal toxicity. , The affinity of different metals to biotic ligands correlates to their toxicity to aquatic organisms .…”
Section: Introductionmentioning
confidence: 99%
“…At a species level there is relatively limited knowledge on the sensitivity and bioaccumulation of pollutants on benthic species (Lister et al, 2015;Alexander et al, 2017;Brown et al, 2017). Heavy-metal studies have shown demonstrated variability within phyla and further research is required before water quality guidelines for the Southern Ocean can be established (Kefford et al, 2019;Webb et al, 2019).…”
Section: Pollution Responsesmentioning
confidence: 99%
“…Consequently, careful thought should be given to the appropriateness of this approach for the contaminant issue in question. A recent example of an appropriate use of the rapid testing approach is provided by Kefford et al () for Antarctic marine invertebrates that are extremely difficult to culture and undertake chronic toxicity testing with in the laboratory.…”
Section: Strengths Limitations and Potential Applications Of Water mentioning
confidence: 99%